Analisis Kesalahan Penggunaan Huruf Kapital pada Tiga Surat dari Pemenang Lomba Menulis Surat untuk Mendikbud - Firda Puspita Cahya; Aida Sofie Rahman; Ezzah Tanisha; M. Bahrul Mafaza; Nazwa Azria Khaifa (Universitas Maritim AMNI Semarang, 2025)
Bahasa Indonesia as an official communication tool had grammatical guidelines such as Ejaan Bahasa Indonesia yang Disempurnakan (EYD) V, which was used to regulate the use of letters, punctuation, and word writing. One important aspect of this grammar was the correct use of capital letters. Unfortunately, there were still many errors in applying this rule, both in scientific and non-scientific writing. This study aimed to analyze the capitalization errors in the three winning letters of the Writing a Letter to the Minister of Education and Culture competition published on the Instagram account @kemdikbud.ri. This research used a qualitative method to examine the errors in capitalization in more depth. The results showed that most errors occurred in using capital letters at the beginning of sentences and proper names, and there were also inappropriate capital letters in the middle of sentences. Further education on capitalization was still needed, especially to improve good and correct writing skills according to Indonesian language guidelines.